Stafne Bone Defect: Report of Two Cases - Münevveroğlu, A. P. (Hindawi Publishing Corporation, 2012)
Stafne bone defects are asymptomatic lingual bone depressions of the lower jaw. In 1942, Stafne described for the first time 35 asymptomatic, radiolucent cavities, unilaterally located in the posterior region of the mandible, between the mandibular angle and the third molar, below the inferior dental canal and slightly above the basis mandibulae. In this study, the clinical and radiological characteristics of 2 cases of Stafne bone defects were described. Orthopantomograph and CBCT were used for diagnosing the defects. The bone defects of two patients in this study were asymptomatic and any other bone lesions, such as cysts and tumors, were excluded because no signs of inflammatory or tumoral changes were evident Therefore, surgery was not considered and the patients were followed for 1 year. Stafne bone defect was an incidental finding, presenting no evolutionary changes, and as such conservatory therapy based on periodic controls was indicated. Currently, complementary techniques such as CT are sufficient to establish a certain diagnosis.